Exploitation de l’Energie Solaire à M’Sila - BOUCHAREB Khaled; enca/IHADDADENE Nabila (University of M'sila, 2024)
In the field of green electricity generation, parabolic trough concentrated solar power technology is acknowledged as one of the most efficient and practicable options. In the first part of this thesis, we studied the viability of building a Concentrating Solar Power plant (CSP) using parabolic trough technology, like the Andasol-1 power plant in southern Spain in the M'Sila region of northern Algeria, through the System Advisor Model (SAM) software. The reference plant has a capacity of 50 MW and contains thermal energy storage (TES) technology. The results showed that when the Andasol-1 plant is installed in M'Sila, it produces electricity all year round from 11h00 a.m. to 17h00, with an average power of between 25 MWe and 50 MWe. When combined, the variables DNI, temperature, and relative humidity account for 98.2 % of the variance in electricity production in M’Sila. The climatic conditions of M’Sila make it favorable to install a CSP plant similar to Andasol-1 since it can produce 177.22 GWh of electricity annually at the M'Sila location. Furthermore, in the second part, the design, analysis and optimization of the performances of a CSP plant based on PTC technology with a capacity of 100 MW equipped with a TES system were carried out, in two sites representatives in Algeria (Tamanrasset and M'Sila). The results of the performance analysis conducted on the optimized design showed that the optimal values of the solar multiple (SM) and full load hours (FLH) of the TES system for the proposed power plant at the M'Sila site are found to be 3 and 7 hours, respectively, with an annual electricity production of 451.84 GWh and a low levelized cost of electricity (LCOE) value of 7.8¢/kWh. The study concluded that the M'Sila site provided encouraging results regarding the deployment of CSP plants integrating PTC technology. M'Sila can reduce demand on its thermal power plant, particularly during summer, by deploying CSP plants with parabolic trough collector technology, which can significantly contribute to the production of clean and sustainable electricity in the long term.
Keywords: Concentrated Solar Power; parabolic trough collector; Andasol-1; M’Sila; SAM.